Faktor-Faktor yang Mempengaruhi Pemanfaatan Posyandu Lansia - Wiwit Desi Intarti; Siti Nur Khoriah (JHeS (Journal of Health Studies), 2018)
Posyandu elderly is a Community Center in the health care effort. The purpose of the research is to analyze the factors of gender, education, employment, family support, and distance support cadres of posyandu service quality towards the utilization of posyandu elderly health centers in the region North of Cilacap II. The type of research that used cross sectional observational approach to know the factors associated with utilization of posyandu elderly. Data analysis using statistical tests of correlation Pearson Product Moment on CI 95%. Statistical tests provide results significantly to gender p 0.182, job=0106, support family p = 0.481, support cadres p=0.443, quality posyandu p=0.558.